Les métaphores conceptuelles dans les synthèmes en -φάγος du grec moderne - Madeleine Voga (Cahiers Balkaniques)
Linguistic categorisation depends not just on our naming of distinctions that exist in the world, but also on our metaphorical and metonymic structuring of our perceptions of the world. In this study, two types of data are examined: inscriptions of compounds in –φάγος from the Reverse Modern Greek Dictionnary (Anastassiadis‑Symeonidis, 2002/2008), e.g. οικοπεδοφάγος “land-eater”, as well as neologisms found in traditional and digital Greek media from 2013 to 2015, e.g. συνταξιοφάγος “pension-eater”. The important productivity of the formation, as well as the link between the semantic interpretation of these units and conceptual metaphors related to the verb τρώγω/φάγω is demonstrated. Conclusions include the acknowledgement that Modern Greek is currently in a period of lexicological change, in line with the important socio-economic change affecting the country since the beginning of the crisis.